Konsentrasi Gas Amoniak (Nh3) Dan Gangguan Kesehatan Pada Pemulung Di TPA Tamangapa Kota Makassar : The Concentration of Ammonia NH3 Gas and Health Problems in Scavengers at the Tamangapa Landfill, Makassar City - Rahma, Andi Nur; Abbas, Hasriwiani Habo; Yuliati, Yuliati; Gafur, Abd (Journal of Aafiyah Health Research (JAHR), 2023)
Background: The waste problem is increasingly complicated in various cities, including Makassar City which is the tenth largest city in Indonesia according to its population, which is 1,449,401 people. Makassar City only has one final disposal site, namely TPA Tamangapa. The percentage of waste volume at TPA Tamangapa which is managed using the Open Dumping method is dominated by organic food waste, which is 38.82%, so the smell and ammonia gas evaporates in the air. Acute effects due to exposure to ammonia at a concentration of 400-700 ppm can cause irritation to the respiratory tract, nose, throat and eyes. Aim: The purpose of this study was to determine the concentration of NH3 in ambient air and the health problems of scavengers at TPA Tamangapa. Method: This type of research is quantitative research with a descriptive approach. Data collection was carried out using a questionnaire of 177 respondents and direct measurement of ambient air using an impinger at TPA Tamangapa in 5 zones. Methods of data analysis using univariate test. . Results: The results showed that the highest ambient air NH3 concentration occurred at night, which was 7.22 mg3/m3, in zone 4, where scavengers live, and the lowest during the day, which was 0.01 mg3/m3, was in zone 5, where the pemlung weighed the waste that had been sorted beforehand. The most health problems were first coughing around 134 people, second was skin irritation around 86 people and third was eye irritation as many as 70 people but there were around 7 people who experienced coughing up blood, these seven people had been scavengers for years. This research requires special attention from the puskesmas in their working area to provide free health services to scavengers because most do not have BPJS cards so if they are sick they do not go for treatment. Conclusion: The concentration NH3 become pollution in the zona 1, 3 and 5, and and the highest disease suffered by scavengers is coughing, skin irritation and also eye irritation.